Insights Into circRNAs: Functional Roles in Lung Cancer Management and the Potential Mechanisms - Feng, Bing; Zhou, Hao; Wang, Ting; Lin, Xinrong; Lai, Yongting; Chu, Xiaoyuan; Wang, Rui (Frontiers in Cell and Developmental Biology, 2021)
Lung cancer is the most prevalent cancer globally. It is also the leading cause of cancer-related death because of the late diagnosis and the frequent resistance to therapeutics. Therefore, it is impending to identify novel biomarkers and effective therapeutic targets to improve the clinical outcomes. Identified as a new class of RNAs, circular RNAs (circRNAs) derive from pre-mRNA back splicing with considerable stability and conservation. Accumulating research reveal that circRNAs can function as microRNA (miRNA) sponges, regulators of gene transcription and alternative splicing, as well as interact with RNA-binding proteins (RBPs), or even be translated into proteins directly. Currently, a large body of circRNAs have been demonstrated differentially expressed in physiological and pathological processes including cancer. In lung cancer, circRNAs play multiple roles in carcinogenesis, development, and response to different therapies, indicating their potential as diagnostic and prognostic biomarkers as well as novel therapeutics. In this review, we summarize the multi-faceted functions of circRNAs in lung cancer and the underlying mechanisms, together with the possible future of these discoveries in clinical application.